Mechanical properties and corrosion behavior of silica nanoparticle reinforced magnesium nanocomposite for bio-implant application - Akm Asif, Iqbal; Norfatihah, Ismail (MDPI, 2022)
In this study, magnesium (Mg)-based nanocomposites reinforced with silica (SiO2) nanoparticles were developed using the powder metallurgy process, and their mechanical and corrosion behavior were assessed. Mg-alloy AZ31 served as the matrix material, and two different weight percentages of SiO2 nanoparticles were used as filler. According to the microstructural analysis, the composite generated a Mg2Si phase as a result of SiO2 dissociating during the sintering process. The microhardness of the Mg-alloy dramatically enhanced with the addition of 3% nanosilica, although the elastic modulus remained constant. Additionally, the outcomes demonstrated that the Mg2Si phase’s development in the composite constrained the mechanism of deterioration and postponed the pace of degradation, which aided in enhancing the qualities of corrosion resistance. This nanocomposite might, thus, be thought of as a potential replacement for the traditional bio-implant materials.